Генеративное развитие видов рода Juniperus L., интродуцированных в Донецком ботаническом саду НАН Украины - Суслова, Е.П. (Промышленная ботаника, 2004)
The results of eleven-year studying of 16 species and forms of the genus Juniperus L. introduced at the Donetsk Botanical Gardens of the National Academy of Sciences of Ukraine are presented. A level of the species’ generative development was determined; morphogenesis peculiarities of generative buds are defined; abnormal pollen seeds are revealed. Pollen fertility of the species investigated has been determined. It was inferred that 11 species of the genus Juniperus are potentially perspective for wide usage in greenery planting and forestry.